DINAMIKA PEMBAHARUAN HUKUM KELUARGA ISLAM DI NEGARA MUSLIM : STUDI ATAS NEGARA MALAYSIA DAN BRUNEI DARUSSALAM - Kholis, Kholis Bidayati; Alwi, Muhammad Alwi Al Maliki; Suci, Suci Ramadhan (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2021)
The intertpersions between Islamic law and Western law that occurred due to colonialism demanded that Muslims reform the law once they were free. This law reform is done in order to maintain the existence of Islamic law. Although in some Muslim countries do not apply the concept of Islamic law traditionally at least in their legal legislation substantively reflects Islamic values. One of them is Malaysia and Brunei Darussalam. Based on the concept of law reform that the two countries did they tried to bring together the point of agreement between Islamic law, western law and customary law in their respective countries.